Hubungan Dinamika Kelompok dengan Tingkat Partisipasi Anggota Kelompok Wanita Tani dalam Program Kawasan Rumah Pangan Lestari (KRPL) di Kecamatan Ampel, Kabupaten Boyolali - Siburian, Sationa Carmelita; Padmaningrum, Dwiningtyas; Suwarto, Suwarto (Universitas Muhammadiyah Semarang, 2023)
Kawasan Rumah Pangan Lestari (KRPL) is a government program for the community in terms of utilizing local resource-based home yards to ensure the sustainable provision of quality and diverse household food. The KRPL program is run by a group of farm women whose implementation requires the participation of farm women in carrying out group activities. Farmer women group members have experienced various ups and downs in group dynamics since its inception. This study aims to determine the dynamics of farm women groups in the KRPL program, determine the level of participation of farm women group members in the KRPL program, and examine the relationship between group dynamics and the level of participation of farm women group members in the KRPL program. Methods of sampling were proportional stratified random sampling with a total of 62 respondents. Data were analyzed using interval width test and Rank Spearman correlation test with IBM SPSS Statistics 25 program. The results showed that there was a significant relationship between group dynamics and the level of participation of farm women group members in the KRPL program including group structure, task function, group atmosphere, group pressure, and hidden agenda.